PyRDFRules : Python wrapper for RDFRules - Douda, Karel; Zeman, Václav; Vojíř, Stanislav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
PyRDFRules is a Python wrapper for interacting with RDFRules, a complex analytical tool for association rule mining in knowledge graphs. RDFRules provides in-built data pre-processing, postprocessing, prediction and optimisations to the AMIE algorithm it utilizes to mine data from the knowledge graphs.
Vedoucí práce: Václav Zeman
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: znalostní a webové technologie [obor dipl. práce]; diplomové práce; master's theses